2015
DOI: 10.1016/j.ijdevneu.2015.04.008
|View full text |Cite
|
Sign up to set email alerts
|

Effect of prenatal stress on memory, nicotine withdrawal and 5HT1A expression in raphe nuclei of adult rats

Abstract: Maternal distress has often been associated with cognitive deficiencies and drug abuse in rats. This study examined these behavioral effects in offspring of mothers stressed during gestation. To this end, pregnant dams were subjected to daily electric foot shocks during the last 10 days of pregnancy. We measured litter parameters and body weights of the descendants after weaning (21 days) and at adulthood (80 days). Afterwards, prenatally stressed and control rats' performances in the novel object recognition … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 67 publications
0
10
0
Order By: Relevance
“…5HT release in target areas is also dependent on the balance of activity on 5HT1A inhibitory autoreceptors on 5HT cell bodies and GABAergic inhibitory interneurons in the DRN. Although neither anxiety nor depressive-like behavior were assessed in the study, the number of 5HT1A receptors (5HT1AR) in the whole DRN region, measured by reversed transcription PCR, was significantly reduced in PS rats (sex not defined) ( Said et al., 2015 ). By means of fluorescence immunohistochemistry with specific antibodies directed to different cell groups, we found that anxiety and depressive-like behavior of PS, Wistar rats was accompanied by a decrease in the expression of 5HT1AR on 5HT cell bodies and GABAergic interneurons in the DRN and PFC in males.…”
Section: Neurochemical Basis Of Behavioral Alterationsmentioning
confidence: 99%
“…5HT release in target areas is also dependent on the balance of activity on 5HT1A inhibitory autoreceptors on 5HT cell bodies and GABAergic inhibitory interneurons in the DRN. Although neither anxiety nor depressive-like behavior were assessed in the study, the number of 5HT1A receptors (5HT1AR) in the whole DRN region, measured by reversed transcription PCR, was significantly reduced in PS rats (sex not defined) ( Said et al., 2015 ). By means of fluorescence immunohistochemistry with specific antibodies directed to different cell groups, we found that anxiety and depressive-like behavior of PS, Wistar rats was accompanied by a decrease in the expression of 5HT1AR on 5HT cell bodies and GABAergic interneurons in the DRN and PFC in males.…”
Section: Neurochemical Basis Of Behavioral Alterationsmentioning
confidence: 99%
“…In addition to data regarding the causal link between inter-individual differences in anxiety- and depression-like behaviors and appetence for nicotine, it was demonstrated that acute stressor exposure through a single episode of intermittent footshock administered 24 h before the start of place conditioning dose-dependently facilitated acquisition of CPP to nicotine in adolescent rats ( 256 ). Prenatal stress in rats also increased nicotine reinforcing properties in a CPP procedure and anxiety withdrawal symptom at the cessation of nicotine exposure ( 257 , 258 ). Finally, chronic mild stress, considered as a model of depression, which was delivered prior to nicotine exposure was found to exacerbate nicotine withdrawal syndrome in rats ( 259 ).…”
Section: Predisposing Endophenotypes For Nicotine Taking and Seeking mentioning
confidence: 99%
“…Among others, impaired adaptation to stressful conditions, increased vulnerability to toxic and traumatic lesions, memory impairments and delayed psychomotor development have been described [43]. Changes in neurotransmitter levels and metabolism, hormonal alterations and gene expression patterns have been documented [12,42,44,45]. In this respect, it is worth mentioning that many neurobehavioral impairments may be related to changes in the dopamine (DA) neurotransmission.…”
Section: Discussionmentioning
confidence: 99%